1985
DOI: 10.1190/1.1441922
|View full text |Cite
|
Sign up to set email alerts
|

The electromagnetic response of an inhomogeneous layered earth—A general one‐dimensional approach

Abstract: The electromagnetic response is studied for a model three‐layer earth formed by constant conductivity in the first and the third layers and conductivity varying with depth in the second layer (i.e., the inhomogeneous transition layer). A generalization to the case of many constant or variable conductivity layers is presented, too. The model problem is addressed by numerically solving an initial value problem for an ordinary differential equation for the inhomogeneous transition layer. The applicability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
1987
1987

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…1). The boundary condition (8) (which replaces (3)) has been determined from the corresponding 1-D problem (Bezvoda and Segeth 1985). The numerical experiments showed that the sizes of the rectangles used are sufficient and cannot influence the results.…”
Section: A Test Example For the V L F Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). The boundary condition (8) (which replaces (3)) has been determined from the corresponding 1-D problem (Bezvoda and Segeth 1985). The numerical experiments showed that the sizes of the rectangles used are sufficient and cannot influence the results.…”
Section: A Test Example For the V L F Methodsmentioning
confidence: 99%
“…Equation (5), with these conditions, can be solved easily (e.g., Cagniard 1953, Praus 1976, Bezvoda and Segeth 1982a, 1985, also in the n-layer case. Equation (5), with these conditions, can be solved easily (e.g., Cagniard 1953, Praus 1976, Bezvoda and Segeth 1982a, 1985, also in the n-layer case.…”
Section: Formulation O F T H E Problemmentioning
confidence: 99%
See 1 more Smart Citation